Case series: Immune checkpoint inhibitor-induced transverse myelitis - Chatterton, Sophie; Xi, Shuo; Jia, Jessica Xi; Krause, Martin; Long, Georgina V.; Atkinson, Victoria; Menzies, Alexander M.; Fernando, Suran L.; Boyle, Thérèse; Kwok, Samuel; Duggins, Andrew; Karikios, Deme; et al. (Frontiers in Neurology, 2023)
Introduction Increasing implementation of the highly efficacious immune checkpoint inhibitors (ICIs) has raised awareness of their various complications in the form of immune-related adverse events (irAEs). Transverse myelitis following ICIs is thought to be a rare but serious neurologic irAE and knowledge is limited about this distinct clinical entity. Cases We describe four patients across three tertiary centers in Australia with ICI-induced transverse myelitis. Three patients had a diagnosis of stage III–IV melanoma treated with nivolumab and one patient had stage IV non-small cell lung cancer treated with pembrolizumab. All patients had longitudinally extensive transverse myelitis on magnetic resonance imaging (MRI) spine and clinical presentation was accompanied by inflammatory cerebrospinal fluid (CSF) findings. Half of our cohort had received spinal radiotherapy, with the areas of transverse myelitis extending beyond the level of previous radiation field. Inflammatory changes on neuroimaging did not extend to the brain parenchyma or caudal nerve roots, except for one case involving the conus medullaris. All patients received high dose glucocorticoids as first-line therapy, however the majority relapsed or had a refractory state (3/4) despite this, requiring escalation of their immunomodulation, with either induction intravenous immunoglobulin (IVIg) or plasmapheresis. Patients in our cohort who relapsed had a poorer outcome with more severe disability and reduced functional independence following resolution of their myelitis. Two patients had no progression of their malignancy and two patients had malignancy progression. Of the three patients who survived, two had resolution of their neurological symptoms and one remained symptomatic. Conclusion We propose that prompt intensive immunomodulation is favored for patients with ICI-transverse myelitis in an attempt to reduce associated significant morbidity and mortality. Furthermore, there is a significant risk of relapse following cessation of immunomodulatory therapy. We suggest one treatment approach of IVMP and induction IVIg for all patients presenting with ICI-induced transverse myelitis based on such findings. With the increasing use of ICIs across oncology, further studies are required to explore this neurological phenomenon in greater detail to help establish management consensus guidelines.